-6x-(-6)-7=-7x+7

Simple and best practice solution for -6x-(-6)-7=-7x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-(-6)-7=-7x+7 equation:


Simplifying
-6x + -1(-6) + -7 = -7x + 7

Multiply -1 * -6
-6x + 6 + -7 = -7x + 7

Reorder the terms:
6 + -7 + -6x = -7x + 7

Combine like terms: 6 + -7 = -1
-1 + -6x = -7x + 7

Reorder the terms:
-1 + -6x = 7 + -7x

Solving
-1 + -6x = 7 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-1 + -6x + 7x = 7 + -7x + 7x

Combine like terms: -6x + 7x = 1x
-1 + 1x = 7 + -7x + 7x

Combine like terms: -7x + 7x = 0
-1 + 1x = 7 + 0
-1 + 1x = 7

Add '1' to each side of the equation.
-1 + 1 + 1x = 7 + 1

Combine like terms: -1 + 1 = 0
0 + 1x = 7 + 1
1x = 7 + 1

Combine like terms: 7 + 1 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| (-x-9i)(x-9i)=0 | | -38=-18-9 | | F(x)=1n(x-2)-4 | | x(3)+9=27 | | X^2+3=5x(x+6) | | 4(3+m)=8(6m+7) | | (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 | | 14x-29=6x+29 | | C=.15M+15 | | 57+66+x=180 | | 1/8logx=-5/3 | | 13-2x=93 | | -5(3x-9)=150 | | 66+x+x=180 | | 1/2X-10=6 | | y^2-8y=20 | | 9x-2=98 | | (-4i)(2i)(-3i)= | | 6/5÷5/8 | | 7(d+2)=2(d-7)+5d | | 2X+Y=356 |

Equations solver categories